(untitled) (Global Journal of Human-Social Science, 2016)
Factors affecting choice decision are location specific and it is also important to look into farmers decision on conservation practices for which they are aware of This study was undertaken in Mt Damota sub-watershed which is among the degraded site in the woreda as well in the zone The study mainly investigated how farmers decide on conservation practices and what determines their decision The data was collected from 103 randomly and proportionately selected households from two PAs and six villages by using stratified random sampling techniques where wealth status was used for the stratification The relevant data were generated using a combination of methods structured questionnaire key informants and group discussion methods as well as secondary data sources Descriptive statistics with appropriate statistical tests and binary logistic regression model were used to analyses the data The study findings from ch-square test showed that the farmers choice decision was positively and significantly correlated to family size educational status social position source and distance of farmland tenure security off-farm income training extension and credit service Factors such as age sex farm size farming experience number of farm plots slope gradient and soil type were not significant The model output showed that factors such as education training tenure security